Fluid power - International Fluid Power Symposium (2nd : 1971 : Guildford, England); Thornton, Wendy A.; Brock, T. E.; Stephens, Herbert Simon; British Hydromechanics Research Association (Cranfield, Eng. : BHRA, 1971)
20